An Analysis of the Efficacy of Platelet-Rich Plasma Injections on the Treatment of Internal Derangement of a temporomandibular Joint - Ismael, Waleed KH; AbdulLateef, Thair; Shumran, Muhannad K (Journal of Baghdad College of Dentistry, 2017)
Background: A Temporomandibular joint (TMJ) internal derangement (TMJID) is a disruption within the internal aspects of the TMJ in which the disc is displaced from its normal functional relationship with the mandibular condyle, after which the articular portion of the temporal bone causes joint dysfunction, joint sound, malocclusion, and locking of the mouth. Conservative and invasive techniques can be used for the treatment of TMJID. A platelet-rich plasma (PRP) injection is a simple, less invasive surgical procedure for the treatment of internal derangement. The objective of this study was to evaluate the efficacy of PRP injections in decreasing or eliminating pain, clicking, and limitation of mouth opening in patients with TMJID after they were proven to be unresponsive to conservative treatments. The aim is to also show more predictable clinical results. Methods: The study involved 70 patients between 19 and 46 years-old, 62 of which were female and 8 of which were male (female to maleratio 7:75).There were a total of 140 joints with anterior disc dislocation with reduction, as confirmed by Magnetic Resonance Imaging (MRI). PRP was injected in the TMJ in the superior joint space. Pain intensity, maximal interincisal opening, and TMJ sounds were assessed and compared for evaluation of treatment success. Results: There was a statistically significant reduction in pain intensity and joint sound and an increase in mouth opening. Conclusions: This study shows that intra-articular PRP injection for the treatment of anterior disc displacement with reduction of the TMJ is a more effective method to reduce pain intensity and joint sound as well as increasing the patient’s mouth opening range